2021
DOI: 10.1186/s13014-021-01857-8
|View full text |Cite
|
Sign up to set email alerts
|

High-dose thoracic radiation therapy for non-small cell lung cancer: a novel grading scale of radiation-induced lung injury for symptomatic radiation pneumonitis

Abstract: Background Symptomatic radiation pneumonitis (RP) may be a serious complication after thoracic radiation therapy (RT) for non-small cell lung cancer (NSCLC). This prospective observational study sought to evaluate the utility of a novel radiation-induced lung injury (RILI) grading scale (RGS) for the prediction of RP. Materials and methods Data of 41 patients with NSCLC treated with thoracic RT of 60–66 Gy were analysed. CT scans were scheduled bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it was impossible to classify them intuitively from the CT images (26). Szejniuk et al reported the RILI grading scale (RGS), and dosimetric parameters were found to be related to changes in RGS severity (27). However, although RGS ranged from 0 to 3, the drawback of poor quantification is also noted.…”
mentioning
confidence: 99%
“…Furthermore, it was impossible to classify them intuitively from the CT images (26). Szejniuk et al reported the RILI grading scale (RGS), and dosimetric parameters were found to be related to changes in RGS severity (27). However, although RGS ranged from 0 to 3, the drawback of poor quantification is also noted.…”
mentioning
confidence: 99%